Electron ray-curable composition, and laminate
The described electron beam curable composition addresses migration and adhesion issues by using specific molecular weight resins and (meth)acrylate compounds, ensuring low migration, strong adhesion, and stability for high-speed printing.
Patent Information
- Application Number
- JP2023181155
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-07
AI Technical Summary
Existing electron beam curable compositions used in food packaging face challenges in meeting strict migration regulatory standards, particularly due to low molecular weight components, and struggle with adhesion to film substrates, film strength, and stability during high-speed printing, leading to issues like peeling and scratching during transportation and printing.
A composition comprising a resin with a weight average molecular weight of 5000 to 50000, a (meth)acrylate compound with a weight average molecular weight of 700 to 3000, and a pigment, without photoinitiators or organic solvents, achieving a balance of low migration, strong adhesion, and film strength, suitable for high-speed printing.
The composition ensures low migration properties, excellent adhesion to film substrates, and resistance to peeling and scratching during transportation, while maintaining high printability and stability during high-speed printing.
Smart Images

Figure 2025010459000001 
Figure 2025010459000002 
Figure 2025010459000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electron beam curable composition and a laminate. [Background technology]
[0002] In recent years, the use of curing technology using active energy rays has expanded in the printing industry because of the following advantages: shortening process time through instant drying, reducing the environmental impact and improving work safety by being non-volatile component (Non-VOC), and realizing strong coating film properties through crosslinking reactions.
[0003] The use of active energy ray curing technology, which began in the field of commercial printing based on paper substrates such as flyers and posters, has spread to various fields due to the development of printing technologies including printing machines and printing inks, and the field of application is expanding to various film substrates, and its use as a packaging material for packaged products such as food, cosmetics, and toys is also expanding.
[0004] In particular, when packaging materials are used for food products, the use of active energy ray curable compositions capable of suppressing migration is essential from the viewpoint of ensuring health safety. Regarding migration in food packaging materials, various regulations have been established to ensure the safety of food packaging. In particular, Swiss Ordinance RS817.023.21 Annex10 establishes a positive list (restrictions on usable raw materials) for packaging materials including non-food contact inks and varnishes, and further regulates the allowable migration amount (SML) for each raw material. The regulation level in the Swiss Ordinance is very strict, but due to the increasing safety consciousness of consumers, the regulation level has become an important indicator as a global standard for food packaging materials in recent years.
[0005] In contrast, when a conventional active energy ray curable composition is used in the application of food packaging materials, it tends to be difficult to meet the above-mentioned SML regulation level. Active energy ray curable compositions are broadly divided into ultraviolet ray curable compositions and electron beam curable compositions from the viewpoint of reaction form. In particular, ultraviolet ray curable compositions require a photoinitiator, and are prone to migration problems due to low molecular weight photopolymerization initiators. On the other hand, electron beam curable compositions do not require a photoinitiator because they use high energy electron beams, and therefore, from the viewpoint of improving migration problems, it is considered that electron beam curable compositions can be preferably used for applications such as food packaging materials.
[0006] However, typical electron beam curable compositions, like ultraviolet curable compositions, contain (meth)acrylate monomers as the main binder component, and are prone to migration problems due to low molecular weight (meth)acrylate monomers. Therefore, even when electron beam curable compositions are used as inks, further studies are required to improve migration.
[0007] Furthermore, in order to meet the diversification and sophistication of consumer needs in recent years, laminates constituting packaging materials have become more diverse and complex, and there is a demand for active energy ray-curable compositions that have good adhesion to a variety of substrate configurations and can form strong coatings.
[0008] However, in the development of an active energy ray-curable composition, there is a proposition that a design that prioritizes adhesion to various film substrates tends to result in a trade-off in which the film strength is deteriorated, and vice versa.
[0009] A related problem is that the printed surface can become scratched or peeled off due to vibrations and friction that occur when packaging materials printed with active energy ray-curable ink are transported by truck or other vehicle, and a solution to this problem is desired.
[0010] Furthermore, in recent years, in order to comply with health safety and environmental regulations, the range of choices for raw materials that can be used as materials for active energy ray-curable compositions has been narrowed, and in particular, active energy ray-curable compositions that do not contain photoinitiators from the viewpoints of health and safety and the presence of persistent organic pollutants such as tetrafluoroethylene are desired.
[0011] Meanwhile, in printing using active energy rays, various printing methods are used, including lithographic printing, flexographic printing, resin letterpress printing, etc. Lithographic printing includes wet lithographic printing, which uses dampening water to form an image by the repulsion of oil (ink) in the printing area and water (dampening water) in the non-printing area, and waterless lithographic printing, which uses a silicone layer in the non-printing area to form an image by the repulsion of the ink in the printing area, and among these, wet lithographic printing, which has good workability, is preferably used.
[0012] Recently, in printing sites, there is a strong demand for shorter delivery times, labor saving, energy saving, and high-speed printing in order to improve production efficiency and reduce costs. Therefore, there is a demand for printing inks that can stably produce high-quality printed matter at high speeds over long periods of time without any trouble, but it is difficult to ensure the necessary viscoelasticity and emulsification performance when made into printing inks, particularly with active energy ray-curable compositions for film substrates, and there are problems such as unstable concentration during high-speed printing and the tendency for smearing to occur during printing, and a solution to these problems is desired.
[0013] Under these circumstances, inks and varnishes, which are active energy ray-curable compositions, have been investigated.
[0014] For example, Patent Document 1 discloses a urethane resin containing an alkyl monoalcohol compound, a polyol compound, and a polyisocyanate compound as essential reaction raw materials. However, the disclosed combination of a binder resin, a (meth)acrylate monomer, and a photoinitiator tends to have insufficient adhesion to a film substrate.
[0015] Patent Document 2 discloses an electron beam curable composition containing a rosin-modified resin, a (meth)acrylate compound, and an extender pigment as essential components. The disclosed electron beam curable composition is expected to improve printability, but has insufficient resistance to scratches and peeling caused by vibration and friction during transportation.
[0016] Patent Document 3 discloses an electron beam curable composition containing, as essential components, an acrylate monomer, an acrylate oligomer, an inactive resin, an acrylated epoxidized vegetable oil, and a white pigment. However, the disclosed electron beam curable composition has a structure developed for use as a primer, and when used in wet lithographic printing in particular, the emulsion balance with the dampening water is poor, and the binder resin needs to be made low molecular weight, so that the viscoelasticity required for the ink cannot be obtained, making it difficult to obtain high-quality printed matter stably over a long period of time.
[0017] Patent Document 4 discloses an active energy ray curable resin composition containing as essential components a urethane (meth)acrylate resin with a specific weight average molecular weight and a (meth)acrylate compound having two types of (meth)acryloyl groups, one to two functional groups and one with three or more functional groups. However, the disclosed active energy ray curable resin composition uses a low molecular weight (meth)acrylate compound as the (meth)acrylate compound other than the urethane (meth)acrylate resin, and when used as a printing ink, there is a concern that the curing property and migration property during high-speed printing may be deteriorated, and further, the stability on the press and the stability during emulsification during water-containing lithographic printing tend to be deteriorated, which is undesirable. [Prior art documents] [Patent documents]
[0018] [Patent Document 1] JP 2019-183012 A [Patent Document 2] JP 2023-028276 A [Patent Document 3] International Publication No. 2020 / 212488 [Patent Document 4] International Publication No. 2020 / 209264 Summary of the Invention [Problem to be solved by the invention]
[0019] An object of the present invention is to provide an electron beam composition which has safety, such as low migration properties, allowing it to be used as a packaging material, and which combines excellent adhesion to film substrates and film strength, thereby reducing problems such as abrasion and peeling during transportation, and has good printability, and a laminate using the electron beam-curable composition. [Means for solving the problem]
[0020] As a result of extensive investigations, the present inventors have found that the above problems can be solved by using the electron beam-curable composition described below, and have thus completed the present invention.
[0021] That is, the present invention relates to an electron beam curable composition comprising a resin (A) having a weight average molecular weight of 5,000 to 50,000, a (meth)acrylate compound (B) having a weight average molecular weight of 700 or more to 3,000 and a weight average molecular weight per (meth)acryloyl group of 100 to 300, and a pigment (C).
[0022] The present invention also relates to the electron beam curable composition described above, wherein the ratio of the content (mass%) of the (meth)acrylate compound (B) in the total amount of the composition to the content (mass%) of the resin (A) in the total amount of the composition is 0.5 to 8.0.
[0023] The present invention also relates to the electron beam curable composition described above, wherein the resin (A) contains at least one resin selected from the group consisting of a rosin-modified resin and a urethane (meth)acrylate resin.
[0024] The present invention also relates to the electron beam curable composition described above, wherein the (meth)acrylate compound (B) contains an amine-modified (meth)acrylate.
[0025] The present invention also relates to the above-described electron beam curable composition, wherein the (meth)acrylate compound (B) contains a polyester (meth)acrylate.
[0026] The present invention also relates to the above-described electron beam curable composition, wherein the total content of the resin (A), the (meth)acrylate compound (B), and the pigment (C) is 60 to 90 mass % based on the total amount of the composition.
[0027] The present invention also relates to the above-mentioned electron beam curable composition, which is characterized by being substantially free of a photopolymerization initiator.
[0028] The present invention also relates to the above-described electron beam curable composition, which is characterized by being substantially free of organic solvents.
[0029] The present invention also relates to the above-mentioned electron beam curable composition, which is substantially free of polytetrafluoroethylene wax.
[0030] The present invention also relates to a laminate comprising a substrate and a cured product of any one of the electron beam-curable compositions described above.
[0031] The present invention also relates to the laminate described above, wherein the substrate is a film or paper.
[0032] The present invention also relates to a method for producing the above-mentioned laminate, which comprises applying any one of the above-mentioned electron beam curable compositions onto a substrate, and irradiating the substrate with an electron beam at an acceleration voltage of 40 to 120 kV and an exposure dose of 10 to 60 kGy. Effect of the Invention
[0033] The present invention has made it possible to provide an electron beam composition which is safe, with low migration properties that enable it to be used in packaging materials, and which also has excellent adhesion to film substrates and film strength, thereby reducing problems such as abrasion and peeling during transportation and has good printability, as well as a laminate using the electron beam-curable composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0034] Hereinafter, an embodiment of the present invention will be described in detail. However, the present invention is not limited to the embodiment described below, and various modifications are possible without departing from the spirit and scope of the present invention.
[0035] In addition, the "conjugated double bond" described in the present invention refers to a bond in which a plurality of double bonds are alternately connected with a single bond in between. However, the π-electron conjugated system contained in an aromatic compound is excluded from the conjugated double bond.
[0036] <Resin (A)> The resin (A) in the present resin has a weight-average molecular weight of 5,000 to 50,000. The type of resin is not particularly limited and any known resin can be used as long as the weight-average molecular weight is 5,000 to 50,000, but a resin that is compatible with and soluble in a (meth)acrylate compound is preferred. If the weight-average molecular weight of the resin is less than 5,000, it is difficult to obtain the necessary ink viscoelasticity when the electron beam curable composition is made into ink, and it is also difficult to obtain emulsification performance when used in wet lithographic printing, which is undesirable. Also, if the weight-average molecular weight exceeds 50,000, it is undesirable because it significantly impairs adhesion to the film. The weight average molecular weight of the resin (A) in the present invention is preferably 10,000 to 25,000.
[0037] As long as the weight average molecular weight of the resin (A) is within the above range, it may or may not contain a (meth)acryloyl group in the molecule.
[0038] Specific examples of the resin (A) include diallyl phthalate resin, rosin-modified resin, polyester resin, epoxy resin, urethane (meth)acrylate resin, polyester (meth)acrylate resin, styrene-acrylic polymer resin, and petroleum resin.
[0039] From the viewpoints of printability, film strength, and adhesion, the resin (A) preferably contains at least one selected from the group consisting of rosin-modified resins and urethane (meth)acrylate resins.
[0040] <Rosin modified resin> The rosin-modified resin in the present invention refers to a resin that contains a skeleton derived from rosin in the resin skeleton.
[0041] The rosin-modified resin in the present invention preferably contains a reaction product of raw material components including rosins, polybasic acids and polyols.
[0042] In the present invention, the rosins refer to monobasic acids having a cyclic diterpene skeleton, and include rosin acid, disproportionated rosin acid, hydrogenated rosin acid, and alkali metal salts of the above compounds. Specific examples of rosins include abietic acid, which has a conjugated double bond, and its conjugated compounds, such as neoabietic acid, palustric acid, and levopimaric acid, as well as pimaric acid, isopimaric acid, sandaracopimaric acid, and dehydroabietic acid, which do not have a conjugated double bond. Examples of natural resins containing these rosins include gum rosin, wood rosin, and tall oil rosin.
[0043] Polybasic acids include carboxylic acids having two or more carboxyl groups in one molecule and their anhydrides.
[0044] Examples of polybasic acids include 1,2,3,6-tetrahydrophthalic acid, 3-methyl-1,2,3,6-tetrahydrophthalic acid, 4-methyl-1,2,3,6-tetrahydrophthalic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, pimelic acid, sebacic acid, azelaic acid, alkenylsuccinic acids such as dodecenylsuccinic acid and pentadecenylsuccinic acid, o-phthalic acid, terephthalic acid, trimellitic acid, pyromellitic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, crotonic acid, isocrotonic acid, and acid anhydrides thereof.
[0045] The polyol may be a compound having two or more hydroxyl groups in one molecule, such as a dihydric alcohol or a trihydric or higher alcohol.
[0046] Examples of the dihydric alcohol include linear alkylene dihydric alcohols such as 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,4-butanediol, 1,2-pentanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-hexanediol, 1,5-hexanediol, 2,5-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,2-octanediol, 1,9-nonanediol, 1,2-decanediol, 1,10-decanediol, 1,12-dodecanediol, 1,2-dodecanediol, 1,14-tetradecanediol, 1,2-tetradecanediol, 1,16-hexadecanediol, and 1,2-hexadecanediol. Branched alkylene dihydric alcohols such as 2-methyl-2,4-pentanediol, 3-methyl-1,5-pentanediol, 2-methyl-2-propyl-1,3-propanediol, 2,4-dimethyl-2,4-dimethylpentanediol, 2,2-diethyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, dimethylol octane, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, and 2,4-diethyl-1,5-pentanediol are also available. Examples of cyclic alkylene dihydric alcohols include 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,2-cycloheptanediol, tricyclodecane dimethanol, hydrogenated catechol, hydrogenated resorcinol, and hydrogenated hydroquinone. Further examples include polyether polyols such as polyethylene glycol (n=2 to 20), polypropylene glycol (n=2 to 20), and polytetramethylene glycol (n=2 to 20), and polyester polyols.
[0047] Further examples of the trihydric or higher alcohols include glycerin, trimethylolpropane, pentaerythritol, 1,2,6-hexanetriol, 3-methylpentane-1,3,5-triol, hydroxymethylhexanediol, trimethylol octane, diglycerin, ditrimethylolpropane, dipentaerythritol, sorbitol, inositol, and tripentaerythritol.
[0048] <Urethane (meth)acrylate resin> The urethane (meth)acrylate resin in the present invention refers to a resin having a urethane bond and a (meth)acryloyl group, which is obtained by reacting an isocyanate group with a hydroxyl group.
[0049] The urethane (meth)acrylate resin in the present invention can be produced according to a method well known in the art. For example, in one embodiment, it may be a compound obtained by reacting a polyisocyanate, a (meth)acrylate having a hydroxyl group, and a polyol in a compounding ratio in which the isocyanate group is in excess.
[0050] In one embodiment, from the viewpoint of easily improving the coating film properties, the urethane (meth)acrylate resin is preferably a compound containing a polyester segment and / or a compound containing a polyether segment. Such a compound is obtained by using a polyether polyol or a polyester polyol as a polyol in the reaction for producing the urethane (meth)acrylate resin.
[0051] Representative compounds that can be used as raw materials for the urethane (meth)acrylate resin will be described below.
[0052] The polyisocyanate is not particularly limited, and examples thereof include tolylene diisocyanate, 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl isocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, Examples of the isocyanate include isocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, xylylene diisocyanate, isophorone diisocyanate, lysine diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, methylcyclohexane diisocyanate, m-tetramethylxylylene diisocyanate, and dimer diisocyanate in which the carboxyl group of a dimer acid is converted to an isocyanate group. From the viewpoint of reaction control, it is preferable that the diisocyanate is bifunctional.
[0053] The (meth)acrylate compound having a hydroxyl group is not particularly limited, and examples thereof include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, polyethylene glycol (meth)acrylate, caprolactone-modified 2-hydroxyethyl (meth)acrylates, glycerin (meth)acrylate, glycerin di(meth)acrylate, and the like. acrylate, diglycerin di(meth)acrylate, diglycerin tri(meth)acrylate, trimethylolpropane (meth)acrylate, trimethylolpropane di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and the like.
[0054] The polyols include glycols, polyether polyols, and polyester polyols.
[0055] Examples of glycols include compounds having two hydroxyl groups, such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, and neopentyl glycol.
[0056] Examples of polyether polyols that can be used include polymers, copolymers, and graft copolymers of alkylene oxides such as tetrahydrofuran, ethylene oxide, propylene oxide, butylene oxide, oxacyclobutane, and oxacycloheptane; and polyether polyols obtained by condensation of hexanediol, methylhexanediol, heptanediol, octanediol, or mixtures thereof, each of which has two or more hydroxyl groups. Furthermore, glycols in which alkylene oxides such as ethylene oxide are added to bisphenols such as bisphenol A and bisphenol F can also be used.
[0057] Examples of polyester polyols include polyester polyols obtained by a condensation reaction between a polyhydric alcohol component and a polybasic acid component.
[0058] As the polyhydric alcohol, at least one of a dihydric alcohol and a trihydric or higher alcohol can be used. The dihydric alcohol is not particularly limited, and linear, branched, or cyclic alkylene dihydric alcohols can be used. Examples of linear alkylene dihydric alcohols include 1,3-propanediol, 1,2-butanediol, 1,4-butanediol, 1,2-pentanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-hexanediol, 1,5-hexanediol, 2,5-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,2-octanediol, 1,9-nonanediol, 1,2-decanediol, 1,10-decanediol, 1,12-dodecanediol, 1,2-dodecanediol, 1,14-tetradecanediol, 1,2-tetradecanediol, 1,16-hexadecanediol, and 1,2-hexadecanediol. Branched alkylene dihydric alcohols such as 2-methyl-2,4-pentanediol, 3-methyl-1,5-pentanediol, 2-methyl-2-propyl-1,3-propanediol, 2,4-dimethyl-2,4-dimethylpentanediol, 2,2-diethyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, dimethylol octane, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, and 2,4-diethyl-1,5-pentanediol are also available. Examples of cyclic alkylene dihydric alcohols include 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,2-cycloheptanediol, tricyclodecane dimethanol, hydrogenated bisphenol A, hydrogenated bisphenol F, hydrogenated bisphenol S, hydrogenated catechol, hydrogenated resorcinol, and hydrogenated hydroquinone.
[0059] The trihydric or higher polyhydric alcohol is not particularly limited, and examples thereof include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, diglycerin, ditrimethylolpropane, sorbitan, sorbitol, dipentaerythritol, inositol, and tripentaerythritol.
[0060] The polybasic acid is not particularly limited, and may be either an aliphatic or alicyclic acid. Examples of aliphatic polybasic acids include alkenylsuccinic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, sebacic acid, azelaic acid, dodecenylsuccinic acid, and pentadecenylsuccinic acid; and examples of aromatic polybasic acids include isophthalic acid, isophthalic acid, terephthalic acid, himic acid, 3-methylhimic acid, 4-methylhimic acid, trimellitic acid, pyromellitic acid, 1,8-naphthalic acid, and anhydrides thereof. Examples of alicyclic polybasic acids include 1,2,3,6-tetrahydrophthalic acid, 3-methyl-1,2,3,6-tetrahydrophthalic acid, 4-methyl-1,2,3,6-tetrahydrophthalic acid, hexahydrophthalic acid, 3-methylhexahydrophthalic acid, 4-methylhexahydrophthalic acid, and anhydrides thereof.
[0061] Furthermore, compounds having three or more hydroxyl groups, such as glycerin, trimethylolpropane, trimethylolethane, pentaerythritol, sorbitol, and methyl glucoside, can also be used as polyols.
[0062] Here, the above-mentioned polyols and polyfunctional alcohols can be used as the polyol without any particular restrictions. They may be used alone or in combination of two or more depending on their respective characteristics. For example, from the viewpoint of the transparency and wet heat resistance of the coating film, it is preferable to use polyether polyols, and it is more preferable to mainly use polyols having a polypropylene glycol skeleton. In addition, from the viewpoint of adhesive strength and heat resistance, it is preferable to use polyester polyols.
[0063] <(Meth)acrylate compound (B)> The (meth)acrylate compound (B) in the present invention is a (meth)acrylate compound having a weight average molecular weight of 700 or more and 3,000 or more, and a weight average molecular weight of 100-300 per (meth)acryloyl group. When the weight average molecular weight and the weight average molecular weight per (meth)acryloyl group are within this range, an excellent balance of low migration properties, film strength, and adhesion is achieved.
[0064] As the (meth)acrylate compound (B) of the present invention, any (meth)acrylate compound having a weight average molecular weight of 700 or more to 3000 and a weight average molecular weight per (meth)acryloyl group of 100 to 300 can be suitably used, but it is preferable to use one or more compounds selected from the group consisting of amine-modified (meth)acrylates, polyester (meth)acrylates, polyether (meth)acrylates, urethane (meth)acrylates, silicone (meth)acrylates, epoxy (meth)acrylates, and epoxidized vegetable oil (meth)acrylates, and it is preferable to include amine-modified (meth)acrylates and / or polyester (meth)acrylates.
[0065] The amine-modified (meth)acrylate in the present invention is a (meth)acrylate compound having one or more amino groups in the molecule.
[0066] The amine-modified (meth)acrylate in the present invention preferably has an amine equivalent of 400 to 2500. When the amine equivalent is 400 to 2500, the surface curability, film strength, and background scumming during wet lithographic printing are all excellent.
[0067] Here, the amine equivalent in the present invention can be calculated as the molecular weight per one active hydrogen derived from the amine in the amine-modified (meth)acrylate.
[0068] The amine-modified (meth)acrylate in the present invention is preferably contained in an amount of 0.5 to 10% by mass based on the total amount of the electron beam curable composition. When the content is within this range, the surface curability, film strength, and background scumming during wet lithographic printing are all excellent.
[0069] Examples of the amine-modified (meth)acrylate in the present invention include EBECRYL LEO 10553 (weight average molecular weight 780, number of acryloyl groups per molecule 4, weight average molecular weight per acryloyl group 195) and EBECRYL 80 (weight average molecular weight 1000, number of acryloyl groups per molecule 4, weight average molecular weight per acryloyl group 250) manufactured by DAICEL-ALLNEX.
[0070] The polyester (meth)acrylate in the present invention is a (meth)acrylate compound having a polyester structure in the molecule (excluding those having an amino group).
[0071] Moreover, the polyester (meth)acrylate in the present invention desirably has 3 to 10 acryloyl groups in the molecule.
[0072] The polyester (meth)acrylate in the present invention is preferably contained in an amount of 10 to 50% by mass based on the total amount of the electron beam curable composition. When the content is 10 to 50% by mass, adhesion, viscoelasticity, and emulsifiability during water-based lithographic printing are all excellent.
[0073] Examples of polyester (meth)acrylates in the present invention include EBECRYL LEO10801 (weight average molecular weight 1500, 6 acryloyl groups per molecule), EBECRYL450 (weight average molecular weight 1600, 6 acryloyl groups per molecule), EBECRYL800 (weight average molecular weight 780, 4 acryloyl groups per molecule), EBECRYL810 (weight average molecular weight 1000, 4 acryloyl groups per molecule), EBECRYL812 (weight average molecular weight 800, 3 acryloyl groups per molecule), EBECRYL846 (weight average molecular weight 1100, 6 acryloyl groups per molecule), and EBECRYL870 (weight average molecular weight 1500, 6 acryloyl groups per molecule), all of which are manufactured by DAICEL-ALNEX.
[0074] From the viewpoint of the viscoelasticity of the ink, it is more preferable to use the (meth)acrylate compound (B) in the present invention in combination with the above-mentioned amine-modified (meth)acrylate and the above-mentioned polyester acrylate.
[0075] In addition, as the (meth)acrylate compound (B) in the present invention, polyether (meth)acrylate, urethane (meth)acrylate, silicone (meth)acrylate, epoxy (meth)acrylate, epoxidized vegetable oil (meth)acrylate, etc. can also be used, and known materials can be used as long as the weight average molecular weight is 700 to 3000 and the weight average molecular weight per (meth)acryloyl group is 100 to 300. Various modified products of these polyether (meth)acrylate, urethane (meth)acrylate, silicone (meth)acrylate, epoxy (meth)acrylate, epoxidized vegetable oil (meth)acrylate, etc. may also be used.
[0076] In the present invention, the ratio of the contents (mass%) of the resin (A) and the (meth)acrylate compound (B) in the total amount of the composition is preferably 0.5 to 8.0, and more preferably 2.0 to 4.0. When the ratio of the contents (mass%) of the resin (A) and the (meth)acrylate compound (B) in the total amount of the composition is 0.5 to 8.0, it is possible to achieve both the necessary adhesion and the viscoelasticity of the ink when made into a water-based lithographic printing ink.
[0077] The pigment (C) in the present invention is a color pigment and an extender pigment. The color pigment in the present invention can be an inorganic pigment or an organic pigment.
[0078] Of the colored pigments in the present invention, specific examples of inorganic pigments include yellow lead, zinc yellow, iron blue, cadmium red, titanium oxide, zinc white, red oxide, ultramarine, carbon black, graphite, and aluminum powder.
[0079] Specific examples of organic pigments among the color pigments in the present invention include soluble azo pigments such as β-naphthol, β-oxynaphthoic acid, β-oxynaphthoic acid arylide, acetoacetic acid arylide, and pyrazolone; insoluble azo pigments such as β-naphthol, β-oxynaphthoic acid arylide, acetoacetic acid arylide monoazo, acetoacetic acid arylide disazo, and pyrazolone; copper phthalocyanine blue; and halogenated (chlorinated or brominated) azo pigments. Examples of suitable pigments include phthalocyanine pigments such as copper phthalocyanine blue, sulfonated copper phthalocyanine blue, and metal-free phthalocyanine; and polycyclic pigments and heterocyclic pigments such as quinacridone pigments, dioxazine pigments, threne pigments (pyranthrone, anthanthrone, indanthrone, anthrapyrimidine, flavanthrone, thioindigo pigments, anthraquinone pigments, perinone pigments, perylene pigments, and the like), isoindolinone pigments, metal complex pigments, and quinophthalone pigments.
[0080] The color pigment in the present invention may be one of these alone or two or more of them in combination, or may be used in combination with one or more extender pigments described below.
[0081] In the present invention, the content of the colored pigment is preferably 2 to 30 mass %, more preferably 5 to 25 mass %, of the total electron beam curable composition in the case of a color ink. In addition, it is preferable that the content of titanium oxide is 30 to 70 mass %, more preferably 40 to 60 mass %, in the case of a white ink. In addition, when preparing a colorless ink, varnish, or a medium for dilution, it is not necessary to contain a colored pigment.
[0082] The extender pigment in the present invention means a pigment that does not have coloring power, and is distinguished from the above-mentioned colored pigment. Specific examples of the extender pigment in the present invention include barium sulfate, alumina white, calcium carbonate, magnesium carbonate, aluminum silicate, magnesium silicate, silicon dioxide, and aluminum hydroxide. These may be used alone or in combination of two or more.
[0083] In addition, the content of the extender pigment in the present invention is preferably 5% by mass or less for the purpose of improving the fluidity and misting resistance of the color ink, and may not be used at all. On the other hand, when used for transparent ink or varnish, it is preferable to use it at 30% by mass or less depending on the application.
[0084] The present invention is also characterized in that the total content of the resin (A), the (meth)acrylate compound (B), and the pigment (C) is 60 to 90% by mass relative to the total amount of the composition. When the electron beam curable composition of the present invention is used as a color ink, the total content is preferably 60 to 80% by mass, more preferably 65 to 75% by mass. When the electron beam curable composition of the present invention is used as a white ink, the total content is preferably 70 to 90% by mass, more preferably 75 to 85% by mass. When the electron beam curable composition of the present invention is used as a varnish or medium, the total content is preferably 60 to 80% by mass, more preferably 65 to 75% by mass. When the total content of the resin (A), the (meth)acrylate compound (B), and the pigment (C) is 60 to 90% by mass relative to the total amount of the composition, the viscoelasticity required for water-based lithographic printing and the necessary printability, such as flowability and transferability, can be obtained.
[0085] In the present invention, (meth)acrylate compounds other than the resin (A) and the (meth)acrylate compound (B) (hereinafter referred to as "other (meth)acrylate compounds") can be used.
[0086] The other (meth)acrylate compounds in the present invention can be appropriately selected depending on the required properties of the cured film, and may be used alone or in combination of two or more kinds.
[0087] In addition, from the viewpoints of curability and low migration, the other (meth)acrylate compounds in the present invention are preferably composed of (meth)acrylate compounds having a weight average molecular weight of 500 or more and having three or more functionalities.
[0088] <Electron beam curing varnish> The electron beam curable composition of the present invention can also be produced from an electron beam curable varnish containing the resin (A).
[0089] The electron beam curable varnish can be prepared using a resin (A) and a (meth)acrylate compound. Although not particularly limited, the electron beam curable varnish preferably contains 10 to 80 mass% of the resin (A) and 20 to 90 mass% of the (meth)acrylate compound, and more preferably contains 20 to 70 mass% of the resin (A) and 30 to 80 mass% of other (meth)acrylate compounds, based on the total mass of the varnish. In this case, the (meth)acrylate compound that can be used may be either the (meth)acrylate compound (B) or another (meth)acrylate compound, so long as the viscosity of the varnish can be adjusted within a desired range.
[0090] The (meth)acrylate compound used in producing the electron beam curable varnish preferably has a weight average molecular weight of 500 or more, from the viewpoint of ensuring low migration properties.
[0091] The electron beam curable varnish of the present invention may contain a photopolymerization inhibitor, which will be described later, in addition to the above components. In such an embodiment, the photopolymerization inhibitor can be added and used by a conventional method. When the photopolymerization inhibitor is added to the varnish, the amount of the photopolymerization inhibitor is preferably 3% by mass or less, more preferably 0.01 to 1% by mass, based on the total mass of the electron beam curable varnish.
[0092] The electron beam curable varnish of the present invention can be produced, for example, by mixing the above components under temperature conditions between room temperature and 160°C. For example, a varnish obtained by heating and melting a rosin-modified resin, dipentaerythritol hexaacrylate, and hydroquinone at a temperature of 100° C. can be suitably used.
[0093] (Polymerization inhibitor) The electron beam curable composition of the present invention may further contain a polymerization inhibitor in addition to the above components. In such an embodiment, the polymerization inhibitor can be added and used by a conventional method. When a polymerization inhibitor is added, the amount of the polymerization inhibitor is preferably 3 mass % or less, more preferably 0.01 to 1 mass %, based on the total mass of the electron beam curable composition, from the viewpoint of not inhibiting the curability.
[0094] Specific examples of polymerization inhibitors include (alkyl)phenols, hydroquinone, catechol, resorcinol, p-methoxyphenol, t-butylcatechol, t-butylhydroquinone, pyrogallol, 1,1-picrylhydrazyl, phenothiazine, p-benzoquinone, nitrosobenzene, 2,5-di-tert-butyl-p-benzoquinone, dithiobenzoyl disulfide, picric acid, cupferron, aluminum N-nitrosophenylhydroxylamine, tri-p-nitrophenylmethyl, N-(3-oxyanilino-1,3-dimethylbutylidene)aniline oxide, dibutyl cresol, cyclohexanone oxime cresol, guaiacol, o-isopropylphenol, butyraldoxime, methyl ethyl ketoxime, cyclohexanone oxime, and di-t-butyl-7-phenylquinone methide. In particular, it is preferable to use one or more compounds selected from hindered amines such as 2,2,6,6-tetraalkylpiperidine derivatives, 2,2,6,6-tetramethylpiperidine derivatives, 1-alkyl-2,2,6,6-tetramethylpiperidine derivatives, and 1-hydro-2,2,6,6-tetramethylpiperidine derivatives, which are compounds having two hydrocarbon groups each at the 2-position and the 6-position on the piperidine ring (four in total), and these can inhibit the curing reaction in a printing machine and provide excellent storage stability.
[0095] (Various additives) The electron beam curable composition of the present invention may further contain various additives such as a viscoelasticity modifier, a dispersant, an anti-friction agent, an anti-blocking agent, and a slip agent depending on the purpose. The various additives can be added to the composition by a conventional method. When various additives are added to the composition, it is preferable to adjust the blending amount within a range that does not inhibit the effects of other components. The blending amount of various additives is preferably 5 mass % or less based on the total mass of the electron beam curable composition.
[0096] Meanwhile, in recent years, there has been concern about global pollution caused by persistent organic pollutants that are difficult to decompose, highly accumulative, mobile over long distances, and harmful (to human health and ecosystems), and regulations are being implemented, as typified by the Stockholm Convention on Persistent Organic Pollutants (POPs Convention) that came into effect in May 2004. For this reason, polytetrafluoroethylene wax used as an anti-friction agent for printing inks may contain persistent organic pollutants such as PFAS, and in the present invention, it is preferable that the present invention is substantially free of polytetrafluoroethylene wax.
[0097] Here, "substantially free" in the present invention means that it is not intentionally added and the content due to unintentional addition is less than 1% by mass. Unintentional addition includes trace amounts contained in each raw material, contamination during the composition manufacturing process, print production process, etc.
[0098] In addition, the electron beam curable composition of the present invention is substantially free of organic solvents. Organic solvents used as viscosity modifiers in printing inks are of concern as they may contain MOSH / MOAH, which are persistent organic pollutants, and since the absence of volatile components (Non-VOC) is expected to reduce the environmental load and improve work safety, it is preferable that the composition of the present invention is substantially free of organic solvents.
[0099] Furthermore, the electron beam curable composition of the present invention does not substantially contain a photopolymerization initiator. While a photopolymerization initiator is expected to have the effect of expressing and improving the curability of an active energy beam curable composition, in the packaging market, particularly in food packaging, toiletry packaging, medical packaging, etc., there is a concern that the safety and quality may be reduced due to migration of the photopolymerization initiator components. Therefore, in the present invention, it is preferable that the composition does not substantially contain a photopolymerization initiator.
[0100] From the viewpoint of carbon neutrality, it is preferable to use, as the various raw materials used in the electron beam curable composition of the present invention, raw materials derived from biomass using renewable resources such as plants.
[0101] When the electron beam curable composition of the present invention is used as a lithographic printing ink, it can be produced by flushing, kneading, and mixing the above-mentioned components under temperature conditions between room temperature and 120° C. In order to produce the ink, it is preferable to use various equipment such as a kneader, a triple roll, an attritor, a sand mill, a gate mixer, etc. In producing the ink, the resin (A) may be added in the form of the resin (A) itself, or in the form of an electron beam curable varnish containing the above-mentioned resin (A).
[0102] <Laminate> In the present invention, the laminate can be obtained by printing the electron beam curable ink on a substrate and curing the ink with an electron beam when the electron beam curable composition is an electron beam curable ink, or by printing the electron beam curable varnish on a substrate, or by printing the electron beam curable varnish on a printed material having ink printed on a substrate, and curing the printed material with an electron beam.
[0103] The substrate usable in the present invention is preferably a film-like substrate, and examples thereof include polyolefin substrates such as polyethylene and polypropylene, polyester substrates such as polyethylene terephthalate and polylactic acid, polycarbonate substrates, polystyrene-based substrates such as polystyrene, AS resin, and ABS resin, nylon substrates, polyamide substrates, polyvinyl chloride substrates, polyvinylidene chloride substrates, cellophane substrates, paper substrates, aluminum substrates, and the like, or film-like substrates made of composite materials thereof. Vapor-deposition substrates in which inorganic compounds such as silica, alumina, and aluminum are vapor-deposited on a polyethylene terephthalate substrate or a nylon substrate can also be used, and the vapor-deposition surface may be further coated with polyvinyl alcohol or the like. The substrate is preferably one in which the surface to be printed (the surface in contact with the printing layer) is subjected to an easy-adhesion treatment, and examples of the easy-adhesion treatment include corona discharge treatment, ultraviolet light / ozone treatment, plasma treatment, oxygen plasma treatment, and primer treatment. In addition, when sufficient adhesion cannot be obtained with a polyethylene terephthalate substrate, it may be subjected to an acrylic coat treatment, polyester treatment, polyvinylidene chloride treatment, and the like.
[0104] The substrate may be a paper substrate. The substrate may be ordinary paper or cardboard, and the thickness of the substrate is not particularly specified. For example, the substrate may have a thickness of 0.2 to 1.0 mm and a thickness of 20 to 150 g / m 2 The above-mentioned can be used, and the printing surface may be easily treated for adhesion. The paper substrate may be surface-deposited with a metal such as aluminum for the purpose of providing a design, or may be surface-coated with an acrylic resin, a urethane resin, a polyester resin, a polyolefin resin, or other resin, and may further be surface-treated with a corona treatment or other treatment. Examples of the paper substrate include coated paper and art paper.
[0105] The printing method of the electron beam curable composition of the present invention is not particularly limited, and known methods can be used. When the electron beam curable composition is an ink, specifically, offset printing with water (normal lithographic printing using dampening water), offset printing without water (lithographic printing without dampening water), resin letterpress printing, screen printing, etc. are used. Among them, offset printing is preferably used, and offset printing with water is more preferably used.
[0106] Similarly, when the electron beam curable composition is a varnish, suitable applications include wet offset printing, waterless offset printing, resin letterpress printing, and screen printing. By adjusting the viscoelasticity, various printing methods such as flexographic printing, gravure printing, and inkjet printing, and coating with various coaters can be selected.
[0107] The electron beam curable composition of the present invention is printed by various printing methods, and then cured through an electron beam irradiator to form a printed layer. The electron beam used for curing is preferably adjusted under the conditions of an acceleration voltage of 40 to 120 kV, preferably 60 to 110 kV, and an exposure dose of 10 to 60 kGy, more preferably 15 to 45 kGy, taking into consideration the balance between damage to the film and the curability of the electron beam curable composition. When the exposure dose is 10 to 60 kGy, sufficient film strength is obtained, and problems due to damage to the film, such as a decrease in film strength, odor, and yellowing, can be suppressed.
[0108] The electron beam curable composition of the present invention can be applied to various substrates and printed materials such as printed materials for forms, printed materials for various books, printed materials for various packaging such as carton paper, printed materials for various plastics, printed materials for stickers / labels, fine art printed materials, and printed materials on metal (fine art printed materials, printed materials on beverage cans, printed materials on canned food such as canned goods). EXAMPLES
[0109] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the present specification, "parts" refers to parts by mass, and "%" refers to % by mass.
[0110] Details of the various measurements carried out in the following examples are as follows.
[0111] (Component analysis of rosin acids) The rosin acids used as raw materials were analyzed by gas chromatography mass spectrometry, and the ratio (%) of each peak area to the total rosin acid peak area (100%) was calculated. More specifically, the content ratio of conjugated rosin acids that undergo a Diels-Alder addition reaction with α,β-unsaturated carboxylic acid or its anhydride (B) and other than the conjugated rosin acids was calculated from the ratio of the corresponding peak areas.
[0112] (Confirmation of the progress of the Diels-Alder addition reaction and quantification of the above-mentioned addition reaction product) The reaction solution of the Diels-Alder addition reaction was analyzed by a gas chromatography mass spectrometer, and the progress of the reaction was confirmed by the decrease in the detection peaks of the rosin acids (a1) and α,β-unsaturated carboxylic acids or their anhydrides (a2) used as raw materials. The reaction was terminated when no change was observed in the decrease in the detection peaks.
[0113] (Measurement of weight average molecular weight) The weight average molecular weight (Mw) was measured using a gel permeation chromatography (HLC-8320) manufactured by Tosoh Corporation. A calibration curve was prepared using a standard polystyrene sample. Tetrahydrofuran was used as the eluent, and three TSKgel SuperHM-M (manufactured by Tosoh Corporation) columns were used. The measurements were performed under the conditions of a flow rate of 0.6 mL / min, an injection volume of 10 μL, and a column temperature of 40°C.
[0114] 1. Preparation of Binder Resin 1-1. Preparation of rosin-modified resin A rosin-modified resin was prepared according to the following recipe. The gum rosin used in the formulation shown below had a conjugated rosin acid content of 80 mass% that undergoes a Diels-Alder addition reaction with an α,β-unsaturated carboxylic acid or an acid anhydride thereof (a2), and a content of acids other than the conjugated rosin acid of 20 mass%.
[0115] (Preparation of Rosin Modified Resin 1) To a four-neck flask equipped with a stirrer, a reflux condenser with a water separator, and a thermometer, 52.9 parts of gum rosin, 37.0 parts of phthalic anhydride, 10.0 parts of glycerin, and 0.1 parts of p-toluenesulfonic acid monohydrate as a catalyst were added, and a dehydration condensation reaction was carried out at 230°C for 6 hours, thereby obtaining rosin modified resin 1.
[0116] (Preparation of Rosin Modified Resin 2) To a four-neck flask equipped with a stirrer, a reflux condenser with a water separator, and a thermometer, 50.0 parts of gum rosin, 41.9 parts of tetrahydrophthalic anhydride, 8.0 parts of glycerin, and 0.1 parts of p-toluenesulfonic acid monohydrate as a catalyst were added, and a dehydration condensation reaction was carried out at 230°C for 7 hours, thereby obtaining rosin-modified resin 2.
[0117] (Preparation of Rosin Modified Resin 3) A four-neck flask equipped with a stirrer, a reflux condenser with a water separator, and a thermometer was charged with 25.0 parts of gum rosin and 15.9 parts of maleic anhydride, and heated at 180°C for 1 hour while blowing in nitrogen gas to obtain a reaction mixture. 38 parts of benzoic acid, 5.0 parts of trimethylolpropane, 16.0 parts of pentaerythritol, and 0.1 parts of p-toluenesulfonic acid monohydrate as a catalyst were added to the reaction mixture, and a dehydration condensation reaction was carried out at 230°C for 9 hours to obtain rosin-modified resin 3.
[0118] (Preparation of Rosin Modified Resin 4) A four-neck flask equipped with a stirrer, a reflux condenser with a water separator, and a thermometer was charged with 27.0 parts of gum rosin and 17.0 parts of maleic anhydride, and heated at 180°C for 1 hour while blowing in nitrogen gas to obtain a reaction mixture. 31.9 parts of benzoic acid, 8.0 parts of trimethylolpropane, 16.0 parts of pentaerythritol, and 0.1 parts of p-toluenesulfonic acid monohydrate as a catalyst were added to the reaction mixture, and a dehydration condensation reaction was carried out at 230°C for 10 hours to obtain rosin-modified resin 4.
[0119] (Preparation of Rosin Modified Resin 5) A four-neck flask equipped with a stirrer, a reflux condenser with a water separator, and a thermometer was charged with 38.5 parts of gum rosin and 27.0 parts of maleic anhydride, and heated at 180°C for 1 hour while blowing in nitrogen gas to obtain a reaction mixture. 11.6 parts of tetrahydrophthalic anhydride, 14.8 parts of glycerin, 8.0 parts of pentaerythritol, and 0.1 parts of p-toluenesulfonic acid monohydrate as a catalyst were added to the reaction mixture, and a dehydration condensation reaction was carried out at 230°C for 12 hours to obtain rosin-modified resin 5.
[0120] (Preparation of Rosin Modified Resin 6) A four-neck flask equipped with a stirrer, a reflux condenser with a water separator, and a thermometer was charged with 37.0 parts of gum rosin and 30.0 parts of maleic anhydride, and heated at 180°C for 1 hour while blowing in nitrogen gas to obtain a reaction mixture. 9.9 parts of tetrahydrophthalic anhydride, 15.0 parts of glycerin, 8.0 parts of pentaerythritol, and 0.1 parts of p-toluenesulfonic acid monohydrate as a catalyst were added to the reaction mixture, and a dehydration condensation reaction was carried out at 230°C for 12 hours to obtain rosin-modified resin 6.
[0121] The formulations and weight average molecular weights of rosin modified resins 1 to 6 are shown in Table 1.
[0122] [Table 1]
[0123] In Table 1, the amounts of each monomer used in preparing the resin (A) are all parts by mass of solid content.
[0124] 1-2. Preparation of urethane (meth)acrylate resin According to the recipe shown below, a urethane (meth)acrylate resin was prepared.
[0125] (Preparation of polyester polyol 1) Into a four-neck flask equipped with a stirrer, a Dean-Stark tube, a thermometer, and a gas inlet tube, 36.2 parts of ethylene glycol and 63.8 parts of adipic acid were placed as raw materials and heated to 220° C. with stirring. The reaction was continued while removing the condensed water generated as the reaction proceeded, and the reaction was terminated when the theoretical amount of dehydration was reached, yielding polyester polyol 1.
[0126] (Preparation of polyester polyols 2 to 6) Polyester polyol resins 2 to 6 were prepared in the same manner as in the preparation of polyester polyol 1, except that the formulation of polyester polyol 1 was changed to the formulations shown in Table 2, respectively.
[0127] [Table 2]
[0128] (Preparation of urethane (meth)acrylate resin 1) In a four-neck flask equipped with a stirrer, a cooler, a thermometer, and a gas inlet tube, 50.4 parts of polyester polyol 1 and 29.3 parts of hexamethylene diisocyanate were placed and reacted with stirring at 100° C. for 3 hours. Next, 20.3 parts of HEA were placed and reacted at 110° C. for an additional 5 hours to obtain urethane (meth)acrylate resin 1.
[0129] (Preparation of urethane (meth)acrylate resins 2 to 6) Urethane (meth)acrylate resins 2 to 6 were prepared in the same manner as for the preparation of urethane (meth)acrylate resin 1, except that the formulations of the urethane (meth)acrylate resins were changed to those shown in Table 3. The weight average molecular weights of the urethane (meth)acrylate resins 1 to 6 are shown in Table 1. Details of the commercially available products used are as follows: HEA: 2-hydroxyethyl acrylate (Osaka Organic Chemical Industry Co., Ltd.)
[0130] [Table 3]
[0131] 1-3. Preparation of polyester resin A polyester resin was prepared according to the following recipe. In a four-neck flask equipped with a stirrer, Dean-Stark tube, thermometer, and gas inlet tube, 10 parts of glycerin, 20 parts of ethylene glycol, and 59 parts of phthalic anhydride were placed as raw materials and heated to 220°C with stirring. As the reaction proceeded, the condensed water produced was removed from the system while the reaction was continued, and when the theoretical amount of dehydration was reached, the reaction was stopped to obtain polyester resin 1. (Weight average molecular weight: 10,500, hydroxyl value 119 KOH / g)
[0132] In addition, the following commercially available resins were used. DAP-K (diallyl phthalate resin, weight average molecular weight 25,000, Osaka Saw Co., Ltd. (Made by Da)
[0133] 2. Preparation of Varnish In a four-neck flask equipped with a stirrer, a Dean-Stark tube, a thermometer, and a gas inlet tube, the raw materials were placed according to the composition in Table 4, heated to 100°C with stirring, and stirred and melted at 100°C for 2 hours to obtain varnishes 1 to 14 in Table 4. Details of the commercially available products used are as follows. Details of the commercially available products used are as follows: Miramer M600: Dipentaerythritol hexaacrylate (weight average molecular weight 578, number of acryloyl groups per molecule: 6, weight average molecular weight per acryloyl group: 96, manufactured by Bigen Specialty Chemical Co., Ltd.)
[0134] [Table 4]
[0135] 3. Preparation of electron beam curable lithographic printing ink and electron beam curable varnish Examples 1 to 27, Comparative Examples 1 to 12 (Preparation of electron beam curable lithographic printing ink and electron beam curable varnish) The ingredients were mixed to obtain the blending ratios shown in Table 5, and milled in a three-roll mill set at 40° C. to obtain the inks and varnishes of Examples 1-27 and Comparative Examples 1-12.
[0136] In addition, the following commercially available materials were used to prepare the inks. FG-7330G: LIONOL BLUE FG-7330G (indigo pigment, manufactured by Toyo Color Co., Ltd.) CR-90-2: Tipaque CR-90-2 (titanium oxide, manufactured by Ishihara Sangyo Kaisha, Ltd.) AEROSIL200V (fumed silica, manufactured by Nippon Aerosil Co., Ltd.) - Hi-Filler #5000PJ (talc, manufactured by Matsumura Sangyo Co., Ltd.) EBECRYL 10551 (amine-modified acrylate, weight average molecular weight: 500, number of acryloyl groups per molecule: 2.5, weight average molecular weight per acryloyl group: 200, manufactured by Daicel-Allnex Corporation) EBECRYL 10553 (amine-modified acrylate, weight average molecular weight: 780, number of acryloyl groups per molecule: 4, weight average molecular weight per acryloyl group: 195, manufactured by Daicel-Allnex Corporation) EBECRYL 80 (amine-modified acrylate, weight average molecular weight: 1,000, number of acryloyl groups per molecule: 4, weight average molecular weight per acryloyl group: 250, manufactured by Daicel-Allnex Corporation) ·Laromer PO 9139 (amine-modified acrylate, weight average molecular weight: 5,900, manufactured by BASF) EBECRYL 851 (polyester acrylate, weight average molecular weight: 500, number of acryloyl groups per molecule: 2.5, weight average molecular weight per acryloyl group: 200, manufactured by Daicel-Allnex Corporation) EBECRYL 800 (polyester acrylate, weight average molecular weight: 780, number of acryloyl groups per molecule: 4, weight average molecular weight per acryloyl group: 195, manufactured by Daicel-Allnex Corporation) EBECRYL 810 (polyester acrylate, weight average molecular weight: 1000, number of acryloyl groups per molecule: 4, weight average molecular weight per acryloyl group: 250, manufactured by Daicel-Allnex Corporation) EBECRYL 450 (polyester acrylate, weight average molecular weight: 1,600, number of acryloyl groups per molecule: 6, weight average molecular weight per acryloyl group: 267, manufactured by Daicel-Allnex Corporation) UF-3007 (polyester acrylate, weight average molecular weight: 3,600, number of acryloyl groups per molecule: 2.5, weight average molecular weight per acryloyl group: 1440, manufactured by Kyoeisha Chemical Co., Ltd.) Miramer M3150 (trimethylolpropane ethylene oxide adduct (15 moles) triacrylate, weight average molecular weight 956, number of acryloyl groups per molecule: 3, weight average molecular weight per acryloyl group: 319, manufactured by MIWON) Miramer M3160 (trimethylolpropane ethylene oxide adduct (6 moles) triacrylate, weight average molecular weight 560, number of acryloyl groups per molecule: 3, weight average molecular weight per acryloyl group: 187, manufactured by MIWON) Polystop 7300P (polymerization inhibitor, Hakuto Co., Ltd.)
[0137] [Table 5]
[0138] [Table 5]
[0139] [Table 5]
[0140] 4. Evaluation of electron beam curable lithographic printing ink and electron beam curable varnish For each of the electron beam curable lithographic printing inks and varnishes prepared in the Examples and Comparative Examples, laminates were prepared according to the following method and the following evaluations were carried out.
[0141] (Transportation vibration test) A laminating adhesive (TM-321A / TM-321B = 2 / 1 manufactured by Toyo-Morton Co., Ltd.) was diluted with ethyl acetate to an active ingredient content of 30 mass % and applied on a PET film (Embret PTM, 12 μm) using a bar coater until the solid content after solvent evaporation at room temperature was 2.0 to 2.5 g / m 2 The resulting laminate was coated so that the adhesive was removed, the solvent was evaporated in a drying oven, and then the laminate was attached to an aluminum foil (7 μm thick, hereinafter AL). Next, the AL foil surface of the resulting laminate was coated with a laminating adhesive in the same manner as above, the solvent was evaporated, and the coated surface was attached to an OPA film (EMBLEM ONM, 15 μm). The OPA film surface of the resulting laminate was coated with a laminating adhesive in the same manner as above, the solvent was evaporated, and the coated surface was attached to the corona-treated surface of an unstretched polypropylene film (FHK2, 40 μm thick, hereinafter CPP, manufactured by Futamura Chemical Co., Ltd.). The obtained laminate was left for 24 hours in an environment of 35°C and humidity of 60% RT to 80% RT. A laminate having a structure of PET / adhesive layer / AL / adhesive layer / OPA / adhesive layer / CPP was obtained.
[0142] The inks and varnishes of Examples 1 to 27 and Comparative Examples 1 to 12 were applied to the PET film surface of the obtained laminate at a concentration of 1 g / m2 relative to the film using an RI tester (a simple color development device manufactured by Akebono Seisakusho Co., Ltd.). 2 The coating film after printing was immediately cured using an electron beam irradiator EC250 / 15 / 180L manufactured by Iwasaki Electric Co., Ltd. at an acceleration voltage of 110 kV and an electron beam dose of 30 kGy to obtain a laminate having a structure of ink layer / PET / adhesive layer / AL / adhesive layer / OPA / adhesive layer / CPP.
[0143] The obtained laminate was used to make a pouch measuring 14 cm x 18 cm, and filled with 150 ml of water. 20 of these pouches were made and placed in cardboard boxes, and transport vibration tests were carried out for 15 minutes in the horizontal direction, 15 minutes in the vertical direction, and 15 minutes in the height direction under conditions of a controlled acceleration of 1 G and a vibration frequency of 6 Hz, and the results were evaluated as follows. The industrially practical level is "3" or higher, with "4" or higher being more preferable.
[0144] (Evaluation criteria for transport vibration test) 5: No scratches or peeling were visually observed on any of the 20 pouches. 4: Scratches or peeling can be visually confirmed in 1 out of 20 pouches. 3: Scratches or peeling are visible in 2 of the 20 pouches. 2: Scratches or peeling are visually confirmed in 3 to 10 of 20 pouches. 1: Scratches or peeling are visible in 11 to 20 of the 20 pouches.
[0145] (Adhesion test) The electron beam curable lithographic printing inks and varnishes of Examples 1 to 27 and Comparative Examples 1 to 12 were each applied to a film at a concentration of 1 g / m using an RI tester (a simple color development device manufactured by Akebono Seisakusho Co., Ltd.).2 The coating was printed so that the coating amount was 100g. The coating film after printing was immediately cured using an electron beam irradiator EC250 / 15 / 180L manufactured by Iwasaki Electric Co., Ltd., at an acceleration voltage of 110kV and an electron beam dose of 30kGy, and the obtained laminate was used to evaluate tape adhesion. Measurements were performed using adhesive tape (cellophane tape (width 12mm) manufactured by Nichiban Co., Ltd.) that was applied to the printed surface and quickly peeled off at an angle of 180 degrees, and the area percentage of the coating film remaining on the printed surface was evaluated on a 5-point scale according to the following criteria. An industrially practical level is "3" or higher, with "4" or higher being more preferable.
[0146] (Adhesion test evaluation criteria) 5: 90% or more of the coating remains 4: The remaining area of the coating is 70% or more but less than 90% 3: The remaining area of the coating is 50% or more but less than 70% 2: The remaining area of the coating is 25% or more but less than 50% 1: Less than 25% of the coating remains
[0147] In addition, the films shown below were used in the adhesion study, but the effects of the present invention are not limited to these films. OPP: FOR (30μm) manufactured by Futamura Chemical Co., Ltd. PE: White polyethylene film (50 μm) PET: Emblet PTM (12μm) manufactured by Unitika Ltd. OPA: Emblem ONM (15μm) manufactured by Unitika Ltd.
[0148] (Migration resistance test) A laminating adhesive (TM-321A / TM-321B = 2 / 1, manufactured by Toyo-Morton Co., Ltd.) was diluted with ethyl acetate to an active ingredient content of 30% and applied to an OPP film (Futamura Chemical Co., Ltd., FOR, 30 μm) using a bar coater until the solid content after solvent evaporation at room temperature was 2.0 to 2.5 g / m 2After the solvent was evaporated in a drying oven, the coated surface was attached to the corona-treated surface of an unstretched polypropylene film (FHK2, 40 μm thick, manufactured by Futamura Chemical Co., Ltd., hereinafter referred to as CPP). Next, the film was left for 24 hours in an environment of 35°C and humidity 60% RT to 80% RT to obtain a laminate having an OPP / adhesive layer / CPP structure.
[0149] The inks of Examples 1 to 27 and Comparative Examples 1 to 12 were applied to the OPP film surface of the obtained laminate at a rate of 2 to 3 g / m2 relative to the film using an RI tester (a simple color development device manufactured by Akebono Seisakusho Co., Ltd.). 2 The printed coating was immediately cured using an Iwasaki Electric EC250 / 15 / 180L electron beam irradiator at an acceleration voltage of 110 kV and an electron beam dose of 30 kGy to obtain a laminate consisting of an ink layer / OPP / adhesive layer / CPP. Next, the resulting printed matter was cut into 3 pieces measuring 9 cm x 9 cm, and the three pieces were stacked so that the printed and non-printed surfaces were in contact with each other, and then 1 kg / dm 2 The three sheets were then placed in a 25°C, 50% humidity environment for 10 days under a load of 1.5 mm. The central printed sheet was then taken out and the non-printed surface area of the sheet was 0.5 mm. 2 The mixture was placed in a migration cell so that it would come into contact with 50 ml of 95% ethanol. The mixture was then stirred and the residual monomers (unreacted (meth)acrylate components) were extracted for 10 days at 60°C. The migration cell was completely sealed with equipment, completely preventing loss of the contents and contamination of the contents (extract) with other components during the above process. Next, a quadrupole-time-of-flight mass spectrometer manufactured by Bruker Daltonics, and The above extracts were analyzed using a Shimadzu LC30A series liquid chromatograph. As the (meth)acrylate component (A) present in ethanol, The concentration of each of the rate compounds was determined. Furthermore, the migration resistance was evaluated according to the following criteria: The industrially practical level is "3" or higher, with "4" or higher being more preferable.
[0150] (Evaluation criteria for migration resistance) 5: (Meth)acrylate component (A) with the highest migration amount (Meth) The concentration of acrylate compounds is less than 10 ppb 4: (Meth)acrylate component (A) with the highest migration amount The concentration of acrylate compounds is 10 ppb or more and less than 25 ppb 3: (Meth)acrylate component (A) with the highest migration amount (Meth) The concentration of acrylate compounds is 25 ppb or more and less than 50 ppb 2: (Meth)acrylate component (A) with the highest migration amount (Meth) The concentration of acrylate compounds is 50 ppb or more and less than 100 ppb. 1: (Meth)acrylate component (A) with the highest migration amount (Meth) The concentration of acrylate compounds is 100 ppb or more.
[0151] <Evaluation of printability> Printing tests were carried out using the inks and varnishes obtained in Examples 1 to 27 and Comparative Examples 1 to 12. The printing tests were carried out on an OPP film (Futamura Chemical Industry's FOR (30 μm)) using a Comexi CI-8 (an offset printing machine manufactured by Comexi). The printing speed was 200 m / min, and the EB irradiation conditions were 110 kV and 30 kGy. In addition, tap water containing 3.0% Sunfort S27H (manufactured by Sunchrmical) was used as the dampening water in the printing test. In order to compare the printing conditions near the boundary of the range of conditions in which normal printing is possible, printing was carried out with a water dial value 2% higher than the lower limit of the water width. Note that the "lower limit of the water width" refers to the minimum amount of dampening water supplied that allows normal printing, and the "water dial" refers to the dial provided on the printing press to adjust the amount of dampening water supplied.
[0152] (Film strength test) The surfaces of the prints obtained by printing the inks of Examples 1 to 27 and Comparative Examples 1 to 12 were rubbed with a cotton swab dipped in a 99.5% ethanol solution at a rate of one stroke per second, and the number of strokes until the surface of the cured film was scraped off was evaluated on a 5-point scale according to the following criteria: "3" or higher is an industrially practical level, with "4" or higher being more preferable. 5: 100+ times 4: 50 to less than 100 times 3: 30 to less than 50 times 2: 10 to less than 30 times Less than 1:10 times
[0153] (High speed printing suitability test) For the inks obtained in Examples 1 to 27 and Comparative Examples 1 to 12, the printing speed was adjusted to the standard density at 100 m / min under fixed conditions other than the printing speed, and then the printing speed was increased to 200 m / min. The initial density stability was evaluated on a 5-point scale based on the density fluctuations observed when 500 m was printed, according to the following criteria: A practical level is "3" or higher, with "4" or higher being more preferable. 5: Concentration fluctuation is less than ±5% 4: Concentration fluctuation is more than ±5% and less than 10% 3: Concentration fluctuation is more than ±10% and less than 15% 2: Concentration fluctuation is more than ±15% and less than 20% 1: Concentration fluctuation is ±20% or more
[0154] (Stain resistance test) In the above printing test, as the printing length increases, ink gradually adheres to the roller supplying dampening water. As the amount of dampening water supplied decreases, ink tends to adhere to the non-image areas (areas where ink should not be) where the image is formed on the printed matter. From these results, as the printing length increases, stains tend to occur on the printed matter. For the above reasons, the water dial was set to a value 2% higher than the lower limit of the water width, and the printed matter was visually inspected and evaluated on a 5-point scale according to the following criteria. A practical level is "3" or higher, with "4" or higher being more preferable. 5: In the 8,000m print, no background stains can be seen on the film. 4: When printing more than 6,000m but less than 8,000m, background scumming occurs in non-image areas. 3: When printing more than 4,000m but less than 6,000m, background scumming occurs in non-image areas. 2: When printing more than 2,000m but less than 4,000m, scumming occurs in non-image areas. When printing at a ratio of less than 1:2,000m, scumming occurs in non-image areas.
[0155] [Table 6]
[0156] As described above, the present invention has provided an electron beam curable composition that provides excellent adhesion to various film substrates, low migration properties and transport resistance that are important in the packaging market, and excellent safety for health and the environment, and a laminate using the electron beam curable composition. In addition, it has been possible to provide an electron beam curable composition that has excellent printability when used as an ink.
Claims
1. The electron beam curable composition includes: a resin (A) having a weight average molecular weight of 5,000 to 50,000; a (meth)acrylate compound (B) having a weight average molecular weight of 700 or more and a weight average molecular weight of 3,000 to 100 per (meth)acryloyl group; and a pigment (C).
2. 2. The electron beam curable composition according to claim 1, wherein a ratio of a content (mass%) of the (meth)acrylate compound (B) in the total amount of the composition to a content (mass%) of the resin (A) in the total amount of the composition is 0.5 to 8.
0.
3. 2. The electron beam curable composition according to claim 1, wherein the resin (A) comprises at least one resin selected from the group consisting of a rosin-modified resin and a urethane (meth)acrylate resin.
4. 2. The electron beam curable composition according to claim 1, wherein the (meth)acrylate compound (B) comprises an amine-modified (meth)acrylate.
5. 2. The electron beam curable composition according to claim 1, wherein the (meth)acrylate compound (B) comprises a polyester (meth)acrylate.
6. 2. The electron beam curable composition according to claim 1, wherein a total content of the resin (A), the (meth)acrylate compound (B), and the pigment (C) is 60 to 90 mass% based on a total amount of the composition.
7. 2. The electron beam curable composition according to claim 1, which is substantially free of a photopolymerization initiator.
8. 2. The electron beam curable composition according to claim 1, which is substantially free of an organic solvent.
9. 2. The electron beam curable composition according to claim 1, which is substantially free of polytetrafluoroethylene wax.
10. A laminate comprising a substrate and a cured product of the electron beam curable composition according to any one of claims 1 to 9.
11. The laminate according to claim 10, wherein the substrate is a film or paper.
12. A method for producing a laminate according to claim 10, comprising applying the electron beam curable composition according to any one of claims 1 to 9 onto a substrate, and irradiating the substrate with an electron beam under conditions of an acceleration voltage of 40 to 120 kV and an exposure dose of 10 to 60 kGy.
Citation Information
Patent Citations
Active ray curable inkjet ink
JP2018178020A
Active energy ray-curable adhesive composition, and laminate
JP2019108426A
Curable composition for inkjet printing, cured product of the same, and electronic component having cured product
JP2019178260A
Electron beam-curable composition and laminate
JP2023028276A
Electron beam-curable composition, and food packaging material
WO2022180887A1